Pharmacokinetic and Pharmacodynamic Modeling of Exendin-4 in Type 2 Diabetic Goto-Kakizaki Rats - Gao, Wei (The American Society for Pharmacology and Experimental Therapeutics, 2011)
The pharmacokinetics (PK) and pharmacodynamics (PD) of exendin-4 were studied in type 2 diabetic Goto-Kakizaki rats after single doses at 0.5, 1, 5, or 10 μg/kg by intravenous administration and 5 μg/kg by subcutaneous administration. Plasma exendin-4, glucose, and insulin concentrations were determined. A target-mediated drug disposition model was used to characterize the PK of exendin-4. Glucose turnover was described by an indirect response model, with insulin stimulating glucose disposition. Insulin turnover was characterized by an indirect response model with a precursor compartment. After intravenous doses, exendin-4 rapidly disappeared from the circulation, whereas it exhibited rapid absorption (T(max) = 15–20 min) and incomplete bioavailability (F = 0.51) after the subcutaneous dose. Exendin-4 increased insulin release at 2 to 5 min with capacity S(max) = 6.91 and sensitivity SC(50) = 1.29 nM, followed by a rebound at 10 to 15 min and a slow return to the baseline. Glucose initially declined because of enhanced insulin secretion, and then gradually increased because of the activation of the neural system by exendin-4. The hyperglycemic action was modeled with increased hepatic glucose production with a linear factor S(RC) = 0.112 1/nM. The mechanistic PK/PD model satisfactorily described the disposition and effects of exendin-4 on glucose and insulin homeostasis in type 2 diabetic rats.